SARS-CoV-2 Exacerbates COVID-19 Pathology Through Activation of the Complement and Kinin Systems - Savitt, Anne G.; Manimala, Samantha; White, Tiara; Fandaros, Marina; Yin, Wei; Duan, Huiquan; Xu, Xin; Geisbrecht, Brian V.; Rubenstein, David A.; Kaplan, Allen P.; Peerschke, Ellinor I.; Ghebrehiwet, Berhane (Frontiers in Immunology, 2021)
Infection with SARS-CoV-2 triggers the simultaneous activation of innate inflammatory pathways including the complement system and the kallikrein-kinin system (KKS) generating in the process potent vasoactive peptides that contribute to severe acute respiratory syndrome (SARS) and multi-organ failure. The genome of SARS-CoV-2 encodes four major structural proteins – the spike (S) protein, nucleocapsid (N) protein, membrane (M) protein, and the envelope (E) protein. However, the role of these proteins in either binding to or activation of the complement system and/or the KKS is still incompletely understood. In these studies, we used: (a) solid phase ELISA, hemolytic assay and surface plasmon resonance (SPR) techniques to examine if recombinant proteins corresponding to S1, N, M and E: (a) bind to C1q, gC1qR, FXII and high molecular weight kininogen (HK), and (b) activate complement and/or the KKS. Our data show that the viral proteins: (a) bind C1q and activate the classical pathway of complement, (b) bind FXII and HK, and activate the KKS in normal human plasma to generate bradykinin and (c) bind to gC1qR, the receptor for the globular heads of C1q (gC1q) which in turn could serve as a platform for the activation of both the complement system and KKS. Collectively, our data indicate that the SARS-CoV-2 viral particle can independently activate major innate inflammatory pathways for maximal damage and efficiency. Therefore, if efficient therapeutic modalities for the treatment of COVID-19 are to be designed, a strategy that includes blockade of the four major structural proteins may provide the best option.